2008
DOI: 10.1248/yakushi.128.617
|View full text |Cite
|
Sign up to set email alerts
|

Step Nonisothermal Method in Kinetics Studies of Captopril Oxidation under Compressed Oxygen

Abstract: A step nonisothermal experiment under high oxygen pressure and a computation with optimization for a step nonisothermal experiment on a stability study of drugs are introduced. The kinetics parameters of captopril oxidation in aqueous solution were determined with this method. It is reported that the reaction of captopril solution occurs under either aerobic or anaerobic conditions, giving diŠerent products. Then the total rate constant k total can be expressed as: k total =k anaerobic +k aerobic =A anaerobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…It has been reported that the oxidation reaction of CPL proceeds owing to oxygen in the atmosphere under high temperature/humidity conditions or after dissolution in water. 4,[34][35][36] In general, semi-solids or liquids have higher molecular mobility than solids resulting in them being chemically unstable. [37][38][39] The CPL-LPR cocrystal hydrate had high hygroscopicity, and when stored under high humidity, the crystal surface adsorbed moisture and became a semi-solid state.…”
Section: Crystengcomm Papermentioning
confidence: 99%
“…It has been reported that the oxidation reaction of CPL proceeds owing to oxygen in the atmosphere under high temperature/humidity conditions or after dissolution in water. 4,[34][35][36] In general, semi-solids or liquids have higher molecular mobility than solids resulting in them being chemically unstable. [37][38][39] The CPL-LPR cocrystal hydrate had high hygroscopicity, and when stored under high humidity, the crystal surface adsorbed moisture and became a semi-solid state.…”
Section: Crystengcomm Papermentioning
confidence: 99%
“…29 Under anaerobic and in aerobic conditions, captopril has been reported to give different products, with disulfide being the major degradation product under aerobic conditions (which is a significant pharmaceutical problem 30 ), and proline is obtained after anaerobic hydrolysis. 31 Sulfur compounds in the physiological environment undergo a variety of metabolic reactions, namely oxidations, reductions, hydrolysis and conjugations. Sulfur in most organic configurations is nucleophilic, and nucleophilic atoms are usually susceptible to metabolic oxidation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Captopril is easily converted to its disulfide dimer and forms conjugates with other thiols . Under anaerobic and in aerobic conditions, captopril has been reported to give different products, with disulfide being the major degradation product under aerobic conditions (which is a significant pharmaceutical problem), and proline is obtained after anaerobic hydrolysis …”
Section: Introductionmentioning
confidence: 99%